1986
DOI: 10.1029/gl013i013p01478
|View full text |Cite
|
Sign up to set email alerts
|

Free oscillations and surface waves of an aspherical Earth

Abstract: The correspondence between free oscillations and surface waves of a laterally heterogeneous earth is established. Starting from the Born approximation of Woodhouse, for large angular order, coupling between neighbouring multiplets along the same dispersion branch leads to the apparent distance shift noted by Woodhouse and Dziewonski, which they obtained from a surface wave approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…The correspondence between free oscillations and surface waves for an isotropic and aspherical earth has been established by Jordan (1978), Woodhouse & Girnius (1982), Woodhouse & Dziewonski (1984) and Mochizuki (1986). In Section 3, these results are extended to the anisotropic case following the procedure of Mochizuki (1986), and the immediate application of our theory is discussed.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The correspondence between free oscillations and surface waves for an isotropic and aspherical earth has been established by Jordan (1978), Woodhouse & Girnius (1982), Woodhouse & Dziewonski (1984) and Mochizuki (1986). In Section 3, these results are extended to the anisotropic case following the procedure of Mochizuki (1986), and the immediate application of our theory is discussed.…”
Section: Introductionmentioning
confidence: 91%
“…In Section 3, these results are extended to the anisotropic case following the procedure of Mochizuki (1986), and the immediate application of our theory is discussed.…”
Section: Introductionmentioning
confidence: 95%
“…The first study on a global scale was that of Woodhouse and Dziewonski (1984) whose global upper-mantle shear velocity models, M84A and M84C, were regarded as reference 3-D model upper-mantle models for the following decade. This was later justified theoretically by Mochizuki (1986aMochizuki ( , 1986b and Romanowicz (1987). Though Woodhouse and Dziewonski used normal mode summation to calculate synthetic seismograms, they used a clever trick to account for sensitivity to odd-degree structure by introducing a fictitious epicentral distance shift in the minor and major arc great circle integrals.…”
Section: Higher Mode Dispersion and Waveform Modelingmentioning
confidence: 99%
“…Thus, the problem lies with the determination of the odd-degree structure. Mochizuki (1986), Romanowicz (1987), and Park (1987) have shown that normal mode amplitudes depend on both the odd-and even-degree structure, and we shall find that amplitudes are more sensitive to odd-degree structure than even-degree structure. Although the frequency range of this study is more limited than that of previous studies, the principal advantages of using normal mode amplitudes as the primary data source are that the determinations of the odd-and even-degree components are essentially decoupled, and the problems facing the recovery of odd-degree earth structure may be better addressed.…”
Section: Introductionmentioning
confidence: 95%